DOES DISCOID MORPHOLOGY AFFECT PERFORMANCE ON RETURN-TO-SPORT TESTING AFTER MENISCUS REPAIR?. Issue 3 (31st March 2019) - Kuba, Megan; Snetselaar, Jordan; Gupta, Andrew; Bompadre, Viviana; Saper, Michael
BACKGROUND: Return-to-Sport (RTS) after knee surgery involves the return of strength and dynamic knee stability, which can be assessed with isometric strength and functional performance testing. There is little evidence-based data to assist with RTS decision-making after meniscus repair. Furthermore, there is limited RTS data comparing patients with discoid meniscus tears and instability from those with non-discoid tears. The purpose of this study was to compare the performance on functional RTS tests between pediatric patients with discoid and non-discoid meniscus tears. METHODS: A retrospective review was performed of pediatric patients that underwent isolated meniscus repair by a single pediatric orthopaedic surgeon from 2010-2016. Thirty patients (14 discoid, 16 non-discoid) were identified who underwent a postoperative RTS assessment consisting of isometric strength testing, the Lower Quarter Y-balance Test (YBT-LQ), and single-leg hop testing (single hop for distance, triple hop for distance, crossover triple hop for distance, and timed hop). Demographic information and RTS data were compared between groups. Recovery of muscle strength was defined by a limb symmetry index (LSI) =90%. Statistical significance was set at P = 0.05. RESULTS: The mean age of the patients was 13.95 years (range, 8-19 years). Patients in the discoid group were younger than those with non-discoid meniscus tears (12.9 vs 15.1 years, respectively) (P =0.05). There was a statistically significant difference in the average time from surgery to RTS test between the discoid (269 days) and non-discoid (184 days) groups. (P =0.02). For isometric strength testing, both groups had mean LSIs greater than 90% for quadriceps, hamstring, and hip abduction. There were no statistically significant differences between groups in isometric strength or performance on the YBT-LQ or any of the single-leg hop tests. CONCLUSIONS: Pediatric patients who undergo repair of a discoid meniscus may require prolonged rehabilitation to achieve satisfactory completion of RTS testing. In our study, an additional 3 months on average were required to allow adequate recovery of muscle strength and dynamic functional stability when compared to those with a non-discoid meniscal repair. However, upon completion of a structured physical therapy program with stringent RTS guidelines, at the time of testing, there was no significant difference in performance on any of the RTS tests between patients with discoid and non-discoid meniscus tears. The findings of this study can assist orthopedic surgeons in safely returning pediatric patients back to sporting activities following meniscus repair.